2017
DOI: 10.1186/s13045-017-0461-8
|View full text |Cite
|
Sign up to set email alerts
|

DEPTOR maintains plasma cell differentiation and favorably affects prognosis in multiple myeloma

Abstract: BackgroundThe B cell maturation process involves multiple steps, which are controlled by relevant pathways and transcription factors. The understanding of the final stages of plasma cell (PC) differentiation could provide new insights for therapeutic strategies in multiple myeloma (MM). Here, we explore the role of DEPTOR, an mTOR inhibitor, in the terminal differentiation of myeloma cells, and its potential impact on patient survival.MethodsThe expression level of DEPTOR in MM cell lines and B cell population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…ILF2 overexpression deregulates homologous recombination (HR) by stabilizing the mRNA splicing of critical HR effectors, which enables genomic instability, promotes adaptive mechanisms to genotoxic stress, and enhances cell survival, thereby promoting drug resistance and disease progression 37 . As regards KB-1471A8.1 , it maps at 8q24 antisense to the 5′ region of DEPTOR , a crucial gene in the maintenance of the terminal differentiation of MM cells 38 . Since the overexpression of DEPTOR in MM has been associated with MAF translocations and the expression of CCND1 and CCND3 genes 39 , the downregulation of KB-1471A8.1 in HD-MM further suggest a cis-regulatory connection with DEPTOR .…”
Section: Discussionmentioning
confidence: 99%
“…ILF2 overexpression deregulates homologous recombination (HR) by stabilizing the mRNA splicing of critical HR effectors, which enables genomic instability, promotes adaptive mechanisms to genotoxic stress, and enhances cell survival, thereby promoting drug resistance and disease progression 37 . As regards KB-1471A8.1 , it maps at 8q24 antisense to the 5′ region of DEPTOR , a crucial gene in the maintenance of the terminal differentiation of MM cells 38 . Since the overexpression of DEPTOR in MM has been associated with MAF translocations and the expression of CCND1 and CCND3 genes 39 , the downregulation of KB-1471A8.1 in HD-MM further suggest a cis-regulatory connection with DEPTOR .…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling of lymphomas from the Emu‐myc transgenic mice identified FAM46C among the genes included in the B lymphocyte developmental signature using the GSEA platform (MSigDB M1487 geneset, Table ). These results suggested that FAM46C might be involved in PC differentiation, so we first quantified FAM46C mRNA levels by qRT‐PCR in four BC populations, immature, naïve, memory B cells and PCs isolated from BM samples obtained from healthy donors . FAM46C expression was significantly higher in PCs than in the earlier stages of differentiation (Figure A, left panel) and was similar in PCs and in HMCLs (Figure A, right panel).…”
Section: Resultsmentioning
confidence: 99%
“…It is found that hsa-mir-642a is over expressed in the pediatric embryonal central nervous system neoplasm that is regarded as a prognostic parameter of patients [ 31 ]. In addition, the abnormal expression of hsa-mir-642a in myeloma cell lines significantly decreased protein levels of DEP domain containing MTOR interacting, which caused dedifferentiation of myeloma cells [ 32 ]. It is noteworthy that hsa-mir-642a is associated with cervical cancer prognosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%